COMPARATIVE ANALYSIS OF COSTS AND TIMES OF RED BRICK AND LIGHT BRICK WORK ON THE MADRASAH MALLIMIN MUALLIMAT TAMBAK BERAS JOMBANG BUILDING PROJECT - Sari, Anindya Novita; Oetomo, Wateno; Marleno, Risma (INTERNATIONAL JOURNAL ON ADVANCED TECHNOLOGY, ENGINEERING, AND INFORMATION SYSTEM, 2024)
The problem in implementing the construction of the Madrasah Muallimin Muallimat Tambak Beras Jombang Building is that the available funds and time are limited. The approach regarding the material needed for this building work is light brick compared to other work items. In wall masonry work using light brick/hebel, it is necessary to analyze whether the work time can be faster and whether the price comparison obtained is cheaper. The research method used is Value Engineering analysis to produce cost savings. The results of this research include: a) Based on the results of cost and time analysis for wall items, namely by proposing alternative materials as replacements for the initial materials, resulting in cost savings of Rp. 28,298,995.61, and b) When compared with productivity, a builder is able to complete a red brick wall in 133 days, whereas with light brick wall material a builder is able to complete the work in 66 days. So, in terms of work speed, lightweight bricks are faster than red brick walls.